THE VIEW OF MOTHERS ON THE HUMANIZATION OF CARE FOR THE CHILD IN PRIMARY HEALTH CARE - Kálya Yasmine Nunes de Lima; Akemi Iwata Monteiro; Ana Dulce Batista dos Santos; Gabriela Bezerra Teixeira (Universidade Federal do Paraná, 2013)
This qualitative study was undertaken in a Family Health Center in 2010 with the objective of discussing the humanization of the care for the child in the view of the mothers, in the light of the National Humanization Policy. The data was collected through a questionnaire administered to 12 mothers accompanying children; the nurse was indicated as the professional who most cares for the child. The lack of privacy during the attendance, the waiting lines, and the environment which is inappropriate for children and their guardians were factors which do not contribute to the humanization of the attendance. There is little encouragement for the mothers to participate in the consultations, and there are flaws in the interpersonal communication between professionals and service users. For the participants, some problems identified in the Center are easy to resolve, the aim being to humanize the care.